Evaluation of antidiabetic activity of ficus deltoidea and schisandra chinensis / Ilyanie Yaacob - Yaacob, Ilyanie (2008)
The antidiabetic potentials of various extracts obtained from the leaves of Ficus deltoidea (Moraceae) and fruits of Schisandra chinensis ( Schisandraceae), the existing plants with no known scientific report on their antidiabetic potentials, were investigated using normoglycemic mice, streptozotocin-induced diabetic rats and obese rats when applicable. The extracts were prepared through maceration of dried powdered leaves and fruits of the respective plants by methanolic solution and subsequently subjecting dried methanolic extract to sequential partition with iihexane, chloroform and n-butanol.